2022
DOI: 10.1183/13993003.01634-2021
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to acid reflux of the airway epithelium in severe asthma

Abstract: BackgroundSevere asthma is associated with multiple co-morbidities, including gastro-oesophageal reflux disease (GORD) which can contribute to exacerbation frequency and poor quality of life. Since epithelial dysfunction is an important feature in asthma, we hypothesised that in severe asthma the bronchial epithelium is more susceptible to the effects of acid reflux.MethodsWe developed an in vitro model of GORD using differentiated bronchial epithelial cells (BECs) from normal or severe asthmatic donors expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…15 This was consistent with the results of an in vitro experiment, which indicated that refluxate exposure could lead to bronchial epithelial damage, barrier leakiness, and/or neutrophil breach of the epithelium, highlighting the crucial role of pepsin in exacerbating asthma. 5 The aforementioned results also indicated the significance of proximal reflux, also known as laryngopharyngeal reflux (LPR), in exacerbating asthma. LPR is characterized by the reflux of gastric acid and refluxate (containing pepsin) above the upper esophageal sphincter.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…15 This was consistent with the results of an in vitro experiment, which indicated that refluxate exposure could lead to bronchial epithelial damage, barrier leakiness, and/or neutrophil breach of the epithelium, highlighting the crucial role of pepsin in exacerbating asthma. 5 The aforementioned results also indicated the significance of proximal reflux, also known as laryngopharyngeal reflux (LPR), in exacerbating asthma. LPR is characterized by the reflux of gastric acid and refluxate (containing pepsin) above the upper esophageal sphincter.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro experiments suggested that pepsin exposure disrupts respiratory epithelium and causes direct contact between submucosal tissue and allergens and pathogens. 5 Thus, pepsin concentration in upper respiratory secretions could be theoretically an indicator of asthma risk. To our knowledge, no study has yet assessed the role of pepsin concentration in pediatric asthma risk.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic comorbidity between asthma and GORD has been widely reported (12; 7), whereas, to the best of our knowledge, evidence for a causal link between these two disorders has not been suggested until now. We used SNP effects as instruments and we provided insights into possible relationships between asthma and GORD; biological explanations explaining such causal relationships might be due to the epithelial dysfunction in asthma, since such patients are more vulnerable to acid reflux (81). Our results also point towards a uni-directional causality from BMI to depression.…”
Section: Discussionmentioning
confidence: 99%
“…(810) Extraesophageal manifestations, include laryngopharyngeal disease (LPR), may lead to complications such as erosive esophagitis (EE) and Barrett’s Esophagus (BE). (1115) An estimated 15% of all visits to otolaryngologists are due to LPR. (16)…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10) Extraesophageal manifestations, include laryngopharyngeal disease (LPR), may lead to complications such as erosive esophagitis (EE) and Barrett's Esophagus (BE). (11)(12)(13)(14)(15) An estimated 15% of all visits to otolaryngologists are due to LPR. (16) GERD can be diagnosed clinically as per the Montreal consensus or it can be defined using invasive testing as per the Porto and Lyon consensus statements.…”
Section: Introductionmentioning
confidence: 99%